Updated study of peripartum cardiomyopathy and preeclampsia - I Gusti Ngurah Agung Trisnu Kamajaya; Made Bagus Dwi Ariyana (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. Cardiovascular disease that occurs during pregnancy is the peripartum cardiomyopathy (PPCM).2. Literature on the association between preeclampsia (PE) and PPCM was reviewed.3. It was not certain whether PE is the independent risk factor of PPCM or an early predictor of PPCM development.   ABSTRACT Objectives: This paper aims to review the literature related to peripartum cardiomyopathy (PPCM) and preeclampsia (PE) in order to know their frequency and relationship and the current knowledge on their pathophysiology and management. Materials and Methods: The articles reviewed in this study were primary clinical studies published around 2016 and 2021, retrieved using Google Scholar and PUBMED databases. After several evaluations, 14-full-text studies written in English were examined. Results: Overall prevalence of PE in PPCM cases varied, about 9.9% - 44% in the individual studies. The lactation hormone prolactin and placental-derived anti-angiogenic factor soluble Fms-like tyrosine kinase 1 (sFlt-1), which had been known to be able to cause cardiac dysfunction, were elevated in both PE and PPCM. This partly explained the pathophysiology that the incidence of concurrent PE in women diagnosed with PPCM was four times more than that in the general population. Conclusion: Epidemiologic studies showed significant overlap between PE and PPCM patients. However, there were not enough good quality data to fully draw conclusions about the relationship between PE and PPCM, whether PE as the independent risk factor of PPCM or an early predictor of PPCM development.